Optimization and Engineering International Multidisciplinary Journal to Promote Optimization Theory & Applications in Engineering Sciences - Sahinidis, Nikolaos V.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Optimization and Engineering is a multidisciplinary journal; its primary goal is to promote the application of optimization methods in the general area of engineering sciences. We expect submissions to OPTE not only to make a significant optimization contribution but also to impact a specific engineering application. Topics of Interest: Optimization: All methods and algorithms of mathematical optimization, including blackbox and derivative-free optimization, continuous optimization, discrete optimization, global optimization, linear and conic optimization, multiobjective optimization, PDE-constrained optimization & control, and stochastic optimization. Numerical and implementation issues, optimization software, benchmarking, and case studies. Engineering Sciences: Aerospace engineering, biomedical engineering, chemical & process engineering, civil, environmental, & architectural engineering, electrical engineering, financial engineering, geosciences, healthcare engineering, industrial & systems engineering, mechanical engineering & MDO, and robotics.
Keywords: Operations research; Decision making; System theory; Mathematical optimization; Engineering; Environmental management; Optimization; Engineering, general; Systems Theory, Control; Environmental Management; Operations Research/Decision Theory; Financial Engineering